High-resolution Ceres High Altitude Mapping Orbit atlas derived from Dawn Framing Camera images. (15th September 2016) - Roatsch, Th.; Kersten, E.; Matz, K.-D.; Preusker, F.; Scholten, F.; Jaumann, R.; Raymond, C.A.; Russell, C.T.
Abstract: The Dawn spacecraft Framing Camera (FC) acquired over 2400 clear filter images of Ceres with a resolution of about 140 m/pixel during the six cycles in the High Altitude Mapping Orbit (HAMO) phase between August 18 and October 21, 2015. We ortho-rectified the images from the first cycle and produced a global, high-resolution, controlled photomosaic of Ceres. This global mosaic is the basis for a high-resolution Ceres atlas that consists of 15 tiles mapped at a scale of 1:750, 000. The nomenclature used in this atlas was proposed by the Dawn team and was approved by the International Astronomical Union (IAU). The full atlas is available to the public through the Dawn Geographical Information System (GIS) web page [http://dawngis.dlr.de/atlas ] and will become available through the NASA Planetary Data System (PDS) (http://pdssbn.astro.umd.edu/ ). Highlights: The mosaic of Ceres was created using camera data from HAMO orbit phase. An atlas of Ceres consisting of fifteen tiles was created. The nomenclature for surface features was approved by the IAU and applied to the atlas.